Economic viability for residential battery storage systems in grid‐connected PV plants. Issue 2 (12th September 2017) - Barcellona, Simone; Piegari, Luigi; Musolino, Vincenzo; Ballif, Christophe
Abstract : Today's residential battery energy storage systems (BESSs) are off the shelf products used to increase the self‐consumption of residential photovoltaic (PV) plants and to reduce the losses related to energy transfer in distribution grids. This work investigates the economic viability of adding a BESS to a residential grid‐connected PV plant by using a methodology for optimising the size of the BESS. The identification of the optimal size which minimises the total cost of the system is not trivial; indeed, it is a trade‐off between OPEX and CAPEX, which are mainly affected by the battery technology, usage profile, expected lifetime, and efficiency. Here, an analysis of the opportunity to install a storage system together with a grid‐connected residential PV plant is performed. Three typical low‐voltage prosumers (Italy, Switzerland, and the UK) are investigated in order to take into account the different legislative and tariff framework over Europe. Numerical results reported here show that present costs of storages are still too high to allow an economic convenience of the storage installation. Moreover, an indication of the necessary incentives to allow the spreading of these systems is given.